Lipase-catalyzed synthesis of 6-o-d-glucosyldecanoate in tert-butanol: reaction optimization and effect of mixing power input - Han, J.; Annuar, M.S.M.; Ariffin, M.F.K.; Gumel, A.M.; Ibrahim, S.; Heidelberg, T.; Bakar, B.; Hossain, A.B.M.S.; Sharifuddin, Y. (2011)
Enzymatic synthesis of 6-O-D-glucosyldecanoate in tert-butanol was performed using substrates D-glucose as acyl acceptor and decanoic acid as acyl donor. Candida antarctica lipase B (Novozyme 435) was used as the catalyst in the esterification process. Box Behnken of response surface methodology (RSM) was used in the optimization of selected parameters viz. reaction temperature, reaction time, substrate ratio and amount of enzyme loading. Substrate ratio was found to be the sole significant main effect while the second-order interaction between reaction time and immobilized enzyme loading was found to be a significant interaction factor. Optimized conditions for the process were: substrate molar ratio 1 (mole acyl donor-to-mole acyl acceptor), 7.5 g·L-1 immobilized enzyme loading, reaction temperature 55°C and time of 14.2 hours. When a mixed-flow impeller with downward pumping mode was used in a stirred tank reactor, minimum power input at 6.8 kW·kg-1 solvent was sufficient for an improved yield of 0.77 g glucosyl decanoate per g glucose. The reaction product composed solely of monoester with sugar acylation occurring at 6-OH primary group of D-glucose where 60 (mole) of the product was 6-O-β-D-glucosyldecanoate and 40 (mole) 6-O-α-D-glucosyldecanoate.